2002
DOI: 10.1007/s00431-002-0919-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-volume peritoneal dialysis in 116 neonatal and paediatric critical care patients

Abstract: early installation of low-volume peritoneal dialysis offers a safe and adequate ultrafiltration procedure for paediatric critical care patients suffering from minor oliguria and fluid overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 18 publications
0
14
0
4
Order By: Relevance
“…In infants with poor cardiac output, bowel perfusion is insufficient to permit adequate dialysis exchange. The capillary permeability of the peritoneal membrane is increased in infants with sepsis; this may lead to more rapid solute removal, but may decrease the ultrafiltration [11][12][13][14]. In patients undergoing PD, we have to estimate the individual peritoneal equilibration rate for optimal dialysis; however, recurrent blood and dialysate sampling can put small infants at additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…In infants with poor cardiac output, bowel perfusion is insufficient to permit adequate dialysis exchange. The capillary permeability of the peritoneal membrane is increased in infants with sepsis; this may lead to more rapid solute removal, but may decrease the ultrafiltration [11][12][13][14]. In patients undergoing PD, we have to estimate the individual peritoneal equilibration rate for optimal dialysis; however, recurrent blood and dialysate sampling can put small infants at additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…The higher mortality rate of our study may be due to our NICU being the only tertiary-level NICU in the southeastern part of the country, where all complicated cases with metabolic diseases, congenital heart defects, and high-risk pregnancies are admitted. Mortality in children suffering from multiorgan system failure was reported to have increased to 60%-70%, regardless of the type of renal replacement therapy performed (25). Therefore, the mortality rate of 71.4% found in our patients suffering from the above-mentioned diseases seems fairly acceptable.…”
Section: Discussionmentioning
confidence: 82%
“…8,9 It has been demonstrated that the use of the low-volume peritoneal dialysis technique (10 mL/kg cycled each hour) and a short indwelling time may have attributed to a low peritoneal irritation and caused less acute hemodynamic disturbances. 8,15,16 In their study, Morris et al found that cardiac index was significantly higher with 10 mL/kg than when the abdomen was empty or contained a larger volume. 17 We also used similar peritoneal dialysis schedule.…”
Section: Discussionmentioning
confidence: 96%